Starbucks’s Fair Trade in The Edge of Globalization - Saomi Rizqiyanto (ETIKONOMI, 2017)
Starbucks as a global company that reflect American values plays an important role in the trade of coffee industry. In February 2000, Starbucks partially adopted the Fair Trade and in early 2001 Starbucks fully adopt Fair Trade. This research seeks to examine the relationship between Starbucks as a symbol of globalization with Starbucks as a global corporation who adopt Fair Trade. This study also seeks to explain how any practical Starbucks Fair Trade as a whole and uncover the reasons behind Starbucks adopt Fair Trade. The research uses a case study method and using a primary and secondary reference sources in the form of books and journals. As a results, this study indicate that Starbucks has strong reasons that ultimately makes the company adopted the Fair Trade. The adoption of Fair Trade also known as CAFE Practices is apparently not spared from criticism of the observer of Fair Trade.DOI: 10.15408/etk.v16i2.5546